Preliminary study of the antibacterial activity of fermented plant extracts against Escherichia coli and bacillus subtilis - Mat Zainal, Nur Fitrah (2017)
Fermented plant extracts from 4 sources of plants Murraya koenigii, Etlingera elatior, Cymbopogon citrates and Citrullus lanatus were examined for their antibacterial activity against Escherichia coli and Bacillus subtilis by using disc diffusion technique. Fermented plant extracts from organic waste is a product produced from fermentation of organic solid waste and it can be used as surfactants, liquid fertilizer, antimicrobial agents, treatment of domestic wastewater, municipal and industrial sludge treatment. Among all of the fermented plant extracts tested, all show positive response to antibacterial activity by showing zone of inhibition after incubation period towards those bacterial strains except for E. elatior that did not show any activity towards B. subtilis. The results shown suggested a potential antimicrobial activity of the fermented plant extracts which may find its application to produce environmental friendly products that act as a surfactant in order to reduce cross contamination in laboratory to occur.